Consequences of the First Wave of the COVID-19 Pandemic in Patients with Chronic Spinal Cord Injury: Impact on Pain, Spasticity and Functionality - Freitas, Margarida Mota; Serviço de MFR do Hospital Garcia de Orta, Almada, Portugal (2022)
Introduction: The disease caused by coronavirus 19 (COVID-19) is an international health emergency and has reached pandemic proportions worldwide. Since March 2020, the Portuguese government implemented measures to prevent the spread of the virus, including almost total temporary suspension of outpatient rehabilitation treatments. Patients with chronic spinal cord injury have an increased risk of developing severe forms of COVID-19 infection. However, they need rehabilitation treatment to control and prevent complications. The aim of this study was to evaluate the impact of the first wave of the COVID-19 pandemic on the clinical evolution of patients with chronic spinal cord injury, regarding pain, spasticity and functionality.Material and Methods: This is a cross-sectional observational study. A telephonic questionnaire was applied to a group of patients with chronic spinal cord injury. The results allowed the comparison of symptoms and functionality before the pandemic and six months after its onset.Results: After exclusion criteria were applied, the sample included a total of 65 participants. All patients who were previously undergoing physiotherapy treatments had to suspend them. Six months after the beginning of the Pandemic in Portugal, 24.6% of the patients reported worsening of pain complaints; 26.2% noted increased spasticity and 21.5% had decreased functionality. In this sample, 12.3% of the patients reported new pressure ulcers or worsening of the previous ones.Patients with cervical spinal cord injury had increased spasticity compared to patients with dorsal or lumbar injury (p=0.003). On the other hand, patients with lumbar spinal cord injury had more frequent worsening of pain complaints (p=0.029). Patients with incomplete motor injury had greater pain worsening when compared to patients with complete injury (p=0.007).Conclusion: The COVID-19 pandemic is having an important impact on the treatment of patients with chronic spinal cord injury, leading to worsening of pain complaints, increased spasticity and decreased functionality. Spasticity worsened more in patients with cervical spinal cord injury while pain worsened more significantly in patients with lumbar injury and incomplete motor injury.